Forecasting using a Nonlinear DSGE Model - Sergey Ivashchenko; Rangan Gupta (Journal of Central Banking Theory and Practice, 2018)
A medium-scale nonlinear dynamic stochastic general equilibrium (DSGE) model was estimated (54 variables, 29 state variables, 7 observed variables). The model includes an observed variable for stock market returns. The root-mean square error (RMSE) of the in-sample and out-of-sample forecasts was calculated. The nonlinear DSGE model with measurement errors outperforms AR (1), VAR (1) and the linearised DSGE in terms of the quality of the out-of-sample forecasts. The nonlinear DSGE model without measurement errors is of a quality equal to that of the linearised DSGE model.
Keywords: E32; E37; E44; E47; 330; Nonlinear DSGE; Quadratic Kalman Filter; Out-of-sample forecasts.